Personalized Postpartum Interventions and Their Impact on Working Mothers - Mey Elisa Safitri; Aniza Abd. Aziz; Nurulhuda Mat Hassan (Media Kesehatan Masyarakat Indonesia, 2025)
Exclusive breastfeeding is a critical determinant in maintaining infant health and nutritional status. However, its coverage remains low, particularly among postpartum working mothers. Limited maternal knowledge, lack of family especially spousal support, and low maternal satisfaction are reported key factors contributing to suboptimal breastfeeding practices. This quasi-experimental study employed a non-equivalent control group pre-test and post-test design. It was conducted from January to October 2024 in the working area of the Darussalam Primary Health Center in Medan, Indonesia. A total of 140 postpartum working mothers were purposively selected and divided into two groups: intervention (n=70) and control (n=70). The intervention group received PBE through a pocketbook, educational videos, and personalized counseling provided by trained midwives. They were followed up at day 7, month 1, month 3 and month 6 post-intervention. Data were analyzed using paired t-test, independent t-test, and repeated measure ANOVA. The exclusive breastfeeding adequacy score significantly increased in the intervention group (p=0.000; p<0.05), indicating meaningful differences across measurement periods. Between-group analysis showed a significant difference (F=11.040; p=0.002; p<0.05). Overall improvements were also significant in maternal knowledge (F=37.238; p= <0.001), maternal satisfaction (F=31.932; p=<0.001), and spousal support (F=26.083; p=<0.001). Personalized breastfeeding edu-cation effectively enhances exclusive breastfeeding adequacy, maternal knowledge and satisfaction, and as well as, and spousal support among postpartum working mothers. Primary health centers and Medan City Health Office are encouraged to integrate personalized breastfeeding education into antenatal and post-natal care programs, involve husbands as active companions, and provide adequate facilities as well as training for breastfeeding-supportive healthcare providers.